Mitos Kecantikan (Ketegangan Citra Perempuan di Bawah Budaya Televisi) - Mardian Sulistyati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
The competition of the television industry in Indonesia creates open spaces for the image of women with the aesthetic standards they create. Television now is no longer just a medium of entertainment but as an ideal female image construction. Beautiful rules are no longer focused on women-only programs but have penetrated the entertainment, religious, reportage, politics, sports, economy, and crime segments. This research is to answer the problem of women's image presented on television, the influence and response are generated; also, the strategies in managing their identity. Applicatively, this research applies the Identity Management Theory pioneered by William R. Cupach and Tadasu Todd Imahori. This theory is used to dismantle the process of identity formed, maintained, and changed in a relationship. This study found several keywords that formulated the concept of managing women's self-identity. These keywords are: force dead/stiff, cornered/alienated; dilemma; and unstable for the context of cultural conflict, and approach; adjustments; and rejuvenation for the completion phase.